An Evaluation of the Postvoid Residual Urine Volume in Acute Stroke Patients in Pakistan - Amjad, Maliha; Bhatti, Muhammad Shahid; Akhtar, Syed Muhammad Hassan; Faisal; Ahmad, Irshad; Siddiqui, Samreen Kibria; Din, Athar ud; Iqbal, Nusrum (Indus Journal of Bioscience Research, 2025)
Background: Postvoid residual urine volume is a critical indicator of bladder dysfunction, particularly in acute stroke patients who may experience neurological impairments affecting urinary control. Objective: This study aims to evaluate postvoid residual urine volume in acute stroke patients and its association with stroke severity, mobility status, and comorbidities. Methods: This prospective observational study was conducted at Shalamar Hospital Lahore during June 2023 to May 2024. A total of 105 patients were added in the study. All demographic data were systematically recorded, including age, sex, stroke type (ischemic or hemorrhagic), stroke location, stroke severity, mobility status, and pre-existing comorbidities such as hypertension and diabetes. Results: The mean age of patients was 58.2 ± 11.8 years, with 63 males (60%) and 42 females (40%). Ischemic stroke was more prevalent (75.2%) compared to hemorrhagic stroke (24.8%). The mean NIHSS score was 14.6 ± 6.1, indicating moderate to severe neurological impairment. High postvoid residual urine volume was observed in 58 patients (55.2%), while 47 patients (44.8%) had normal postvoid residual urine volume. Among ischemic stroke patients, 20 (24.1%) had high postvoid residual urine volume, whereas 7 (28%) of hemorrhagic stroke patients exhibited high postvoid residual urine volume. Conclusion: Postvoid residual urine volume is significantly elevated in many acute stroke patients, with over half experiencing urinary retention. This is strongly linked to stroke severity, reduced consciousness, and impaired mobility. Non-ambulatory patients face a higher risk, highlighting the impact of neurological deficits and physical inactivity on bladder dysfunction, emphasizing the need for targeted management strategies.